Profiling systems and computer based technology in performance diagnosis -- their practice use in improving the quality of answers concerning sociomedical issues and statements as well as the planning of medical and vocational rehabilitation. - Schian H; Kaiser H (Rehabilitation, 2000)
Systems for comparing ability and requirement profiles as well as instruments for evaluating functional capacity are current topics in rehabilitation. Only few of them however are related to vocational rehab. This article describes the present state of affairs in the development in procedures, instruments and methods to measure work-related human functional capacity with the aim of vocational rehabilitation and integration, helping to obtain objective results to decide about further steps. They are an addition to sociomedical advice in assessment and vocational centres, and serve to expand the common basis of the WHO International Classification of impairments, disabilities and handicaps (ICIDH). The purpose is intervention. Abilities are contrasted with requirements, as the basis for defining a need for intervention and realizing appropriate action. This is the thinking integrated in the German profiling assessment and documentation system IMBA--Integration von Menschen mit Behinderungen in die Arbeitswelt (Integration of people with disabilities into worklife). Diagnostic, computer based technology and work simulation and measurement to evaluate functional capacity as developed and used in the U.S. is complementary to IMBA. Work simulation is based on databases, such as the D.O.T., and includes standardized work requirement profiles. Such systems have been imported from the United States of America to Switzerland and the Netherlands and now to Germany. There are numerous connections with German assessment systems, and the fundamentals of ICIDH are included. Common application in the field of rehabilitation is dealt with, also in view of pensioning issues. The need for user training and quality management are reported in this article as well.